A resistência em Clarice Lispector: uma aprendizagem - Ferreira, Bianca Pulgrossi (Universidade Federal de São Carlos, 2018)
The object of study of this work is the novel An Apprenticeship or The Book of Delights, published in 1969, by the writer Clarice Lispector. The main objective is to show that this novel can be considered a “resistance narrative”, according to Alfredo Bosi (2002). For that, we present a study of part of the critical fortune of the author, followed by a reflection on the concept of “resistance” and its connection with the historical context of the military regime of 1964. Finally, we are going to use these elements to compose a final analysis, showing that resistance operates in the novel through ironic and parodistic elements destabilizing norms, values and interpersonal and social conditioning, intensified in the period in question and aimed at destabilizing its reception. Thus, we intend to present a new reading perspective on the novel, which emphasizes its social-political character, in order to position the writer as a critic of her time.
The resistence in Clarice Lispector: an apprenticeship
Keywords: Literatura brasileira; Resistência; Lispector, Clarice, 1920-1977; Brazilian literature; Resistance; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES